The Need to Consider Food Systems in Health-Oriented Food Policy and Programs - Alanna K Higgins (Current Developments in Nutrition)
Produce prescription programs (PPPs) are place-based interventions at the intersection of public health and local food advocacy. These programs have expanded significantly across the United States since 2010, particularly taking off in the state of West Virginia. This article draws on a 4-y institutional ethnography of PPP programs and associated policy. Although the possibilities of building support for improving community health alongside the livelihoods of small-scale producers is compelling, there exists an overall decontextualization from broader social and political determinants of health. This article concludes that although programs are able to meet some acute needs for program participants and provide income for small-scale producers, this decontextualization results from a lack of consideration of wider systems within policy and program construction, leading to missed opportunities for food system transformation.